1998
DOI: 10.1046/j.1365-2346.1998.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses, arterial oxygen saturation and plasma catecholamine concentration during upper gastrointestinal endoscopy using conscious sedation with midazolam or propofol

Abstract: Hypoventilation as a consequence of deep intravenous sedation is the most frequently reported cause of cardiac arrest during upper gastrointestinal endoscopy (UGIE). Haemodynamic stress can contribute to myocardial ischaemia; therefore, this study was designed to observe prospectively the cardiorespiratory changes during UGIE using either midazolam or propofol for conscious sedation. Thirty-four patients, aged 50 years and older, ASA physical status I-III, scheduled for elective UGIE with sedation, were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…In several studies, the classical metabolic endocrine response has been obtained with upper gastrointestinal endoscopy (12,17). In the present study, serum cortisol, glucose and CRP levels increased during endoscopy, although the increments were not statistically significant.…”
Section: Discussioncontrasting
confidence: 48%
“…In several studies, the classical metabolic endocrine response has been obtained with upper gastrointestinal endoscopy (12,17). In the present study, serum cortisol, glucose and CRP levels increased during endoscopy, although the increments were not statistically significant.…”
Section: Discussioncontrasting
confidence: 48%
“…Later, during the surgery, the difference may perhaps be explained by the greater B ¼ estimated parameter value; SE ¼ error of estimated parameter value; df ¼ degrees of freedom; Exp (B) ¼ ODDS probability ⁄ -probability; zSBP ¼ systolic blood pressure after normalizing data; zNA ¼ serum noradrenaline level after normalizing data; zCortisol ¼ serum cortisol level after normalizing data. incidence of pain in the TA group (Oei-Lim et al 1998). However, against this we found that, even after excluding data for those patients who experienced any pain at all, the difference in SBP was still significantly higher in the TA group.…”
Section: Analysis Of Changes In Blood Pressurementioning
confidence: 50%
“…Hypertension and tachycardia caused by pain cause myocardial ischemia in patients undergoing procedures performed under conscious sedation. 33 In a large study of safety and efficacy in office-based plastic surgery, Byrd et al 21 found that the most common serious anesthetic complications were cardiac-related. However, few studies have evaluated the efficacy of sedation protocols to control hemodynamic parameters.…”
Section: Discussionmentioning
confidence: 99%